Research progress and application prospects of flexible wearable sensor in spacesuit - Aiming Bu; Wanxin Zhang; Qian Ran; Dongyue Liu; Jialu Ma; Rongqing Wang; Kun Shang; Hongrui Yang; Zhiqiang Mei (Sensing and Bio-Sensing Research)
Spacesuit provide the basic life support for astronauts in the space environment. Astronauts in extravehicular operations need spacesuit for pressure to form a vacuum protection. However the suit pressure caused greater joint activity resistance impact on the operation of astronauts. The wearable sensors have drawn more and more attention because its operations are simple and real-time detections are available. It can realize the benefits of heart rate, breathing, sweat, action recognition and date acquisition, etc. The joint resistance characteristics of spacesuit is revealed under pressure were studied by wearing flexible wearable sensors, which provides a theoretical basis for improving the performance of spacesuit. Based on the above problems, this paper summarizes the latest research progress of wearable flexible sensor category and application of different types of flexible sensors. Finally, the challenges in the application of flexible wearable sensors in the spacesuit were discussed. It provides a theoretical basis for the research in related fields.